Structure and density of basaltic melts at mantle conditions from first-principles simulations - Bajgain, Suraj (Nat Commun, 2015)
The origin and stability of deep-mantle melts, and the magmatic processes at different times of Earth's history are controlled by the physical properties of constituent silicate liquids. Here we report density functional theory-based simulations of model basalt, hydrous model basalt and near-MORB to assess the effects of iron and water on the melt structure and density, respectively. Our results suggest that as pressure increases, all types of coordination between major cations and anions strongly increase, and the water speciation changes from isolated species to extended forms. These structural changes are responsible for rapid initial melt densification on compression thereby making these basaltic melts possibly buoyantly stable at one or more depths. Our finding that the melt-water system is ideal (nearly zero volume of mixing) and miscible (negative enthalpy of mixing) over most of the mantle conditions strengthens the idea of potential water enrichment of deep-mantle melts and early magma ocean.